The Potential of Ladle Slag and Electric Arc Furnace Slag use in Synthesizing Alkali Activated Materials; the Influence of Curing on Mechanical Properties - Mark Češnovar (Materials, 2019)
Alkali activation is studied as a potential technology to produce a group of high performance building materials from industrial residues such as metallurgical slag. Namely, slags containing aluminate and silicate form a useful solid material when activated by an alkaline solution. The alkali-activated (AA) slag-based materials are promising alternative products for civil engineering sector and industrial purposes. In the present study the locally available electric arc furnace steel slag (Slag A) and the ladle furnace basic slag (Slag R) from different metallurgical industries in Slovenia were selected for alkali activation because of promising amorphous Al/Si rich content. Different mixtures of selected precursors were prepared in the Slag A/Slag R ratios 1/0, 3/1, 1/1, 1/3 and 0/1 and further activated with potassium silicate using an activator to slag ratio of 1:2 in order to select the optimal composition with respect to their mechanical properties. Bending strength of investigated samples ranged between 4 and 18 MPa, whereas compressive strength varied between 30 and 60 MPa. The optimal mixture (Slag A/Slag R = 1/1) was further used to study strength development under the influence of different curing temperatures at room temperature (R.T.), and in a heat-chamber at 50, 70 and 90 °C, and the effects of curing time for 1, 3, 7 and 28 days was furthermore studied. The influence of curing time at room temperature on the mechanical strength at an early age was found to be nearly linear. Further, it was shown that specimens cured at 70 °C for 3 days attained almost identical (bending/compressive) strength to those cured at room temperature for 28 days. Additionally, microstructure evaluation of input materials and samples cured under different conditions was performed by means of XRD, FTIR, SEM and mercury intrusion porosimetry (MIP).